2007
DOI: 10.1348/000709907x189118
|View full text |Cite
|
Sign up to set email alerts
|

University students' academic performance: An integrative conceptual framework and empirical analysis

Abstract: Our study provides support for the key mediational role of study strategies in the effect of achievement goals and self-efficacy on academic performance. Self-efficacy seems to have the strongest indirect effect on performance. Mastery goals play a key role increasing deep processing and effort, and in turn affecting performance. Academic performance tends to diminish with increasing class size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
229
2
32

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(316 citation statements)
references
References 92 publications
39
229
2
32
Order By: Relevance
“…Other studies identified students' attitude/interest in the course as one of the factors which have got a profound effect on the academic achievement (Ali, 2013;Fenollar et al, 2007;Mekonnen, 2014 Social related factors have also been recogonised by a number of studies to have notable effects on academic performance (Thamavithya, (n.d.); Umar, Shaib, Aituisi, Yakubu, & Bada, 2010). University life can be stressful, though it is without doubt one of the most memorable experiences in a student's life.…”
Section: Related Literature On Factors Affecting Student Performancementioning
confidence: 99%
“…Other studies identified students' attitude/interest in the course as one of the factors which have got a profound effect on the academic achievement (Ali, 2013;Fenollar et al, 2007;Mekonnen, 2014 Social related factors have also been recogonised by a number of studies to have notable effects on academic performance (Thamavithya, (n.d.); Umar, Shaib, Aituisi, Yakubu, & Bada, 2010). University life can be stressful, though it is without doubt one of the most memorable experiences in a student's life.…”
Section: Related Literature On Factors Affecting Student Performancementioning
confidence: 99%
“…Investigadores de ciencias de la salud y de otras disciplinas han intentado identificar de qué forma, variables tradicionales de ingreso a la universidad, notas de secundaria, así como variables demográ-ficas y estilos de aprendizaje, contribuyen al desempeño académico de pregrado 1,[3][4][5][6][7][8][9][10] . Existen estudios que han centrado el análisis en algunas variables 4,5,11,12 ; mientras que otros han intentado responder a la pregunta a través del contraste de variables y diseño de modelos de predicción más complejos [13][14][15][16][17][18] .…”
Section: N V E S T I G a C I ó N Rev Méd Chile 2009; 137: 1291-1300unclassified
“…Edad, sexo, resultados en entrevistas de admisión, experiencia académica previa, experiencias con temas de salud previa, personalidad y motivación se relacionan con rendimiento académico 13,17 . En otras carreras de pregrado, los estilos de aprendizaje 15 , las creencias de los estudiantes 18 y variables de contexto 16 , se relacionan con rendimiento acadé-mico.…”
Section: N V E S T I G a C I ó N Rev Méd Chile 2009; 137: 1291-1300unclassified
See 2 more Smart Citations